First in line : presidents, vice presidents, and the pursuit of power - Brower, Kate Andersen (Harper, an imprint of HarperCollinsPublishers, 2018)
Explores the lives and roles of thirteen vice presidents of the modern era, discussing the complicated relationship between president and vice president and how this connection influenced each vice president's political future.